Reading Auden as a Resource for Existential Reflection in a Society with Technocratic and Hedonistic Tendencies - Martina Pavlikova (Communications - Scientific letters of the University of Zilina, 2017)
The aim of this paper is to highlight the importance of a remarkable writer, Wystan Hugh Auden (1907 - 1973), who was strongly influenced by the philosophy and thinking of the Danish philosopher, Soren Kierkegaard, especially by his works Either - Or, The Concept of Anxiety, Works of Love and The Sickness Unto Death. Auden’s poetry is noted for its stylistic and technical achievement, its engagement with politics, morals, love, purity and religion, and its unique variety in tone, form and content. It is enormously rich in allusions, poetic tone and intellectual power. The content of his poems ranges from philosophical meditations, the concept of being, the concept of man, anxiety, aloneness and despair, to the contemporary crises of modern man and the evolution of society. His poetry becomes a resource for existential reflection in modern society with the technocratic and hedonistic tendencies of consumer society of which this paper is an in-depth analysis.